Perlindungan konsuler warga negara ganda dalam konflik bersenjata - Muhammad Adrian fitra yamazaki; Aldo kurniawan; Qyan Hari Simartla Gudangga; Fadel Jovinka (GLOBAL SCIENTS PUBLISHER, 2026)
Consular protection for dual nationals during armed conflict remains an inadequately addressed gap in international law. This study attempts to examine how the international legal framework regulates consular protection for dual nationals during armed conflict, while also mapping the various obstacles that arise in its implementation in the field. To address this issue, this study uses a normative legal research method by combining legislative, conceptual, and case studies, sourced from a literature review of primary, secondary, and tertiary legal materials. The results of the study found that the legal basis for consular protection is essentially based on the 1963 Vienna Convention on Consular Relations and the 1961 Vienna Convention on Diplomatic Relations, but neither instrument specifically addresses the issue of dual nationality. Consequently, the determination of which country is entitled to provide protection is left to the principle of effective nationality, which in practice is often applied inconsistently. This complexity is further compounded during armed conflict, as access for consular officials is limited, diplomatic relations can be disrupted, and administrative procedures become cumbersome. The 1949 Geneva Conventions do provide minimum protection through international humanitarian law, but they cannot completely replace consular protection. The case of Aiden Aslin in 2022 illustrates how the ambiguity of dual citizenship can lead to the loss of effective access to consular protection in conflict zones.